Solvability for a Fractional Order Three-Point Boundary Value System at Resonance - Zigen Ouyang; Hongliang Liu (Abstract and Applied Analysis)
A class of fractional order three-point boundary value system with resonance is investigated in this paper. Using some techniques of inequalities, a completely new method is incorporated. We transform the problem into an integral equation with a pair of undetermined parameters. The topological degree theory is applied to determine the particular value of the parameters so that the system has a solution.